2021
DOI: 10.1371/journal.pone.0256427
|View full text |Cite
|
Sign up to set email alerts
|

The hunter and the hunted—A 3D analysis of predator-prey interactions between three-spined sticklebacks (Gasterosteus aculeatus) and larvae of different prey fishes

Abstract: Predator-prey interactions play a key life history role, as animals cope with changing predation risk and opportunities to hunt prey. It has recently been shown that the hunting success of sticklebacks (Gasterosteus aculeatus) targeting fish larvae is dependent on both the size of the prey and the prior exposure of its species to stickleback predation. The purpose of the current study was to identify the behavioural predator-prey interactions explaining the success or failure of sticklebacks hunting larvae of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…We found that both predator distance and prey acceleration in the moments until the attack were highly predictive of predation success, with targeted prey that were further away, and that showed a faster acceleration response, being more likely to evade capture. These two features have also been found as significant variables affecting survival in a study on predator-prey dynamics with single prey ( Walker et al, 2005 ; see also Lucas et al, 2021 ). Together, this suggests that targeted prey could sometimes anticipate the strike, highlighting that, despite the very high speeds pike attained, prey response does matter in predator-prey dynamics, and that evasive prey behaviour may be especially successful when prey are further away (see also Ranåker et al, 2012 ).…”
Section: Discussionmentioning
confidence: 86%
“…We found that both predator distance and prey acceleration in the moments until the attack were highly predictive of predation success, with targeted prey that were further away, and that showed a faster acceleration response, being more likely to evade capture. These two features have also been found as significant variables affecting survival in a study on predator-prey dynamics with single prey ( Walker et al, 2005 ; see also Lucas et al, 2021 ). Together, this suggests that targeted prey could sometimes anticipate the strike, highlighting that, despite the very high speeds pike attained, prey response does matter in predator-prey dynamics, and that evasive prey behaviour may be especially successful when prey are further away (see also Ranåker et al, 2012 ).…”
Section: Discussionmentioning
confidence: 86%
“…Cette population de poissons, introduite au xix e siècle et originellement cantonnée à la zone littorale, connaît une explosion démographique et un changement d'habitat, préférant désormais l'habitat pélagique au point de devenir dominant dans cette zone. Ce changement d'écologie d'une espèce clé se traduit par un accroissement de la prédation sur les oeufs et les stades larvaires des corégones (Baer et al, 2021 ;Lucas et al, 2021), sur les ressources planctoniques, baissant fortement le niveau de recrutement des corégones, et par la réémergence, malgré le niveau resté très bas des concentrations en phosphore, de la cyanobactérie filamenteuse toxique typique des lacs alpins Planktothrix rubescens 22 .…”
Section: Restaurations Trophiques : Succès Rémissions éChecsunclassified